Frozen dispersions of nanomaterials are a useful operational procedure in nanotoxicology. Issue 1 (2nd January 2017) - Vila, Laura; Rubio, Laura; Annangi, Balasubramanyam; García-Rodríguez, Alba; Marcos, Ricard; Hernández, Alba
Abstract: The variability observed in nanoparticle (NP) dispersions can affect the reliability of the results obtained in short-term tests, and mainly in long-term experiments. In addition, obtaining a good dispersion is time-consuming and acts as a bottleneck in the development of high-throughput screening methodologies. The freezing of different aliquots from a stock dispersion would overcome such limitations, but no studies have explored the impact of freezing thawing the samples on the physico-chemical and biological properties of the nanomaterial (NM). This work aims to compare fresh-prepared and frozen MWCNT, ZnO-, Ag-, TiO2- and CeO2 -NP dispersions, used as models. NP characterization (size and morphology by TEM), hydrodynamic size and zeta potential were performed. Viability comparisons were determined in BEAS-2B cells. Cellular NP uptake and induced ROS production was assessed by TEM and flow cytometry, respectively. The obtained results show no important differences between frozen and fresh NP in their physico-chemical characteristics or their biological effects. This study is the first to demonstrate that there is no scientific evidence to dismiss the use of frozen NP, opening the door to the development of short- and long-term experiments with higher consistency, accuracy and reproducibility in a much shorter time and using a simplified procedure.